2014
DOI: 10.1021/es500065z
|View full text |Cite
|
Sign up to set email alerts
|

Low Cytotoxicity of Inorganic Nanotubes and Fullerene-Like Nanostructures in Human Bronchial Epithelial Cells: Relation to Inflammatory Gene Induction and Antioxidant Response

Abstract: The cytotoxicity of tungsten disulfide nano tubes (INT-WS2) and inorganic fullerene-like molybdenum disulfide (IF-MoS2) nanoparticles (NPs) used in industrial and medical applications was evaluated in comparison to standard environmental particulate matter. The IF-MoS2 and INT-WS2 reside in vesicles/inclusion bodies, suggestive of endocytic vesicles. In cells representing the respiratory, immune and metabolic systems, both IF-MoS2 and INT-WS2 NPs remained nontoxic compared to equivalent concentrations (up to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 35 publications
3
68
0
Order By: Relevance
“…Thus, INT-WS 2 are low-cost, environmentally friendly and biocompatible nanollers since they possess much lower cytotoxicity than other nanoparticles like silica or carbon black. 16 Taking advantage of their properties, advanced polymer/INT nanocomposites with different morphologies, such as epoxy/INT-WS 2 and poly(methyl methacrylate) (PMMA)/INT-WS 2 nanobers have been successfully developed. 17,18 More speci-cally in the eld of biodegradable and renewable thermoplastics, we have recently demonstrated that the incorporation of INT-WS 2 offers new possibilities to improve the crystallization and mechanical performance of these polymers in order to compete with increasingly expensive petroleum based materials.…”
Section: ) and 1993mentioning
confidence: 99%
“…Thus, INT-WS 2 are low-cost, environmentally friendly and biocompatible nanollers since they possess much lower cytotoxicity than other nanoparticles like silica or carbon black. 16 Taking advantage of their properties, advanced polymer/INT nanocomposites with different morphologies, such as epoxy/INT-WS 2 and poly(methyl methacrylate) (PMMA)/INT-WS 2 nanobers have been successfully developed. 17,18 More speci-cally in the eld of biodegradable and renewable thermoplastics, we have recently demonstrated that the incorporation of INT-WS 2 offers new possibilities to improve the crystallization and mechanical performance of these polymers in order to compete with increasingly expensive petroleum based materials.…”
Section: ) and 1993mentioning
confidence: 99%
“…Their optical properties allow various other applications in fields such as nanolithography or photocatalysis [19]. Equally important, the cytotoxicity of the INT-WS 2 was evaluated positively in comparison to standard environmental particulate matter, demonstrating much lower cytotoxicity than other nanoparticles, such as silica or carbon black [20]. Promising results have also been recently found with respect to the biocompatibility of INT(IF)-WS 2 with salivary gland cells [21].…”
Section: Introductionmentioning
confidence: 99%
“…tungsten oxide and H 2 S or sulfur) are relatively inexpensive. In addition, INT-WS 2 (or IF-MoS 2 ) are low-cost, environmentally friendly and biocompatible nanofillers with much lower cytotoxicity than other nanoparticles, such as silica or carbon black [28]. Positive results were recently also obtained in testing the biocompatibility of INT(IF)-WS 2 with salivary gland cells, suggesting promising future medical applications of these nanoparticles [29].…”
Section: Introductionmentioning
confidence: 99%